Development of methodological training of future teachers based on the integration of pedagogical and information technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
This article examines the content, legislative framework and current state of pedagogical and information technology integration in improving the methodological training of future teachers and promoting a potential educator through this